STABILITY ANALYSIS OF A SHALLOW SLOPE FAILURE DURING RAINY SEASON IN KULONPROGO, INDONESIA - Agus Setyo Muntohar, Eko Soebowo (SLOPE, 2015)
In Indonesia, landslides commonly occurred during the rainy season in December to March. In this period, the rainfall intensities were very high and precipitated continuously. A case history of shallow landslide type in Kulonprogo, Indonesia is presented in this paper. The slope experienced to shallow failure on 21 November 2001, and the after that slope is prone to movement during the wet season in December to February every year. The aim of the paper is to evaluate the slope stability, in term of the probability of failure, during the wet season from 2004 to 2012. A probabilistic model of stability analysis incorporating infiltration was computed in this study. Direct Monte Carlo Simulation (MCS) method was performed to obtain the failure probability. The results show that the failure probability of the slope ranges from 0.126 to 0.302. The lowest and highest probability of failure was obtained for the rainfall period of December 2009 â€“ March 2010 and December 2005 â€“ March 2006 respectively. The performance level of the studied slope can be classified as â€œhazardousâ€. In general, the study concludes that the proposed model can be applied to the preliminary analysis of slope stability during the wet season.